2022
DOI: 10.2196/36100
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiepitope Vaccine Against SARS-CoV-2: Immunoinformatics Study

Abstract: Background Since the first appearance of SARS-CoV-2 in China in December 2019, the world witnessed the emergence of the SARS-CoV-2 outbreak. Due to the high transmissibility rate of the virus, there is an urgent need to design and develop vaccines against SARS-CoV-2 to prevent more cases affected by the virus. Objective A computational approach is proposed for vaccine design against the SARS-CoV-2 spike (S) protein, as the key target for neutralizing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The allergenicity prediction via the AlgPred server showed that the multi-epitope vaccine was non-allergen, while the server VaxiJen v2.0 with the default parameters and the threshold 0.4 [ 54 ] demonstrated its probable antigenicity with the antigenic score 0.4656.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The allergenicity prediction via the AlgPred server showed that the multi-epitope vaccine was non-allergen, while the server VaxiJen v2.0 with the default parameters and the threshold 0.4 [ 54 ] demonstrated its probable antigenicity with the antigenic score 0.4656.…”
Section: Resultsmentioning
confidence: 99%
“…The allergenicity prediction via the AlgPred server showed that the multi-epitope vaccine was non-allergen, while the server VaxiJen v2.0 with the default parameters and the threshold 0.4 [54] demonstrated its probable antigenicity with the antigenic score 0.4656. and subsequently refined by GalaxyRefine (Figure 4). The tool generated five models out of which the one with the better characteristics was selected for the docking analysis.…”
Section: Physicochemical Properties Allergenicity and Antigenicity An...mentioning
confidence: 99%
“…More than 100 manuscripts are accessible in NCBI PubMed database (https://pubmed. ncbi.nlm.nih.gov/) in which the Institute has contributed to SARS-CoV-2 publications, including basic, preclinical and clinical studies [19][20][21][22] , bioinformatics and in silico studies [23][24][25] , case reports [26,27] , reviews, and meta-analysis [18,28] , as well as publications on COVID-19 mechanisms [29,30] , long COVID [31,32] , and COVID-19 diagnosis and therapeutic targets [33][34][35][36] . However, only a few of these publications have been cited in this manuscript.…”
Section: Conduction Of Applied and Basic Researchmentioning
confidence: 99%
“…VaxiJen v2.0 was applied to predict the antigenicity of the multi-epitope protein construct (Doytchinova and Flower, 2007a,b). The threshold was set as 0.4, and default parameters were employed (Ghafouri et al, 2022).…”
Section: Vaccine Properties-in Silico Assessmentmentioning
confidence: 99%